Co-expression analysis suggests lncRNA-mRNA interactions enhance antiviral immune response during acute Chikungunya fever in whole blood of pediatric patients - de Souza Felix, Juliana [UNESP]; Almeida, Mariana Cordeiro [UNESP]; da Silva Lopes, Maria Fernanda [UNESP]; de Athayde, Flávia Regina Florencio [UNESP]; Troiano, Jéssica Antonini [UNESP]; Scaramele, Natália Francisco [UNESP]; de Oliveira Furlan, Amanda [UNESP]; Lopes, Flavia Lombardi [UNESP] (Public Library of Science (PLoS), 2023)
Chikungunya virus is an arbovirus that causes the neglected tropical disease chikungunya fever, common in tropical areas worldwide. There is evidence that arboviruses alter host transcriptome and modulate immune response; this modulation may involve transcriptional and post-transcriptional control mechanisms mediated by long non-coding RNAs (lncRNAs). Herein, we employed bioinformatic analysis to evaluate co-expression of lncRNAs and their putative target mRNAs in whole blood during natural Chikungunya infection in adolescent boys. Sequencing data from GSE99992 was uploaded to the Galaxy web server, where data was aligned with HISAT2, gene counts were estimated with HTSeq-count, and differential expression was run with DESeq2. After gene classification with Bio-mart, Pearson’s correlation was applied to identify potential interactions between lncRNAs and mRNAs, which were later classified into cis and trans according to genomic location (FEELnc) and binding potential (LncTar), respectively. We identified 1,975 mRNAs and 793 lncRNAs that were differentially expressed between the acute and convalescent stages of infection in the blood. Of the co-expressed lncRNAs and mRNAs, 357 potentially interact in trans and 9 in cis; their target mRNAs enriched pathways related to immune response and viral infections. Out of 52 enriched KEGG pathways, the RIG-I like receptor signaling is enriched by the highest number of target mRNAs. This pathway starts with the recognition of viral pathogens, leading to innate immune response mediated by the production of IFN-I and inflammatory cytokines. Our findings indicate that alterations in lncRNA expression in adolescent boys, induced by acute Chikungunya infection, potentially modulate mRNAs that contribute to antiviral immune responses.